Relating dynamic perception of reformulated cheese pies to consumers' expectations of satiating ability. (December 2015) - Marcano, J.; Varela, P.; Cunha, L.M.; Fiszman, S.
Abstract: Designing satiating food is not an easy task. Food reformulation is normally done by altering the proportion of basic ingredients or by adding new minor ingredients. In general, the texture varies concomitantly with these changes, altering the way the food is processed orally and the complete eating experience. This highlights the interest of discovering how variations in minor ingredients influence texture and how this affects the dynamics of the oral trajectory. Six cheese pie formulations were prepared: basic recipe ( Base ), no egg ( − Egg ), no corn starch ( − Corn starch ) no sugar ( − Sugar ), added diary cream (+  Cream ) and extra skimmed milk powder (+  Milk powder ). Temporal dominance of sensations was used to show that the appearance and disappearance of each texture sensation dominance experienced in the mouth during the eating process differed among the six pies, as did their relation to the consumers' expectation of satiating capacity scores and to the changes in composition. Two extreme behaviors were found: suppression of egg/addition of extra milk powder made the pies initially drier and harder, while suppression of corn starch/addition of cream gave the samples a soft, moist early sensation. The former elicited higher expectations of satiating capacity. In addition, overall liking, liking evolving with time (dynamic liking) and the level of several key texture attributes' divergence from those of an "ideal" cheese pie were evaluated on bipolar just-about-right scales and through penalty analysis to gain insights into potential directions for reformulating acceptable pies. Highlights: Minor changes in reformulated cheese pies affect temporal texture perception. Early texture sensations seemed to play a role on satiating expectations. Too soft and moist textures are less liked and elicit weaker satiating expectations. Liking tests indicate a texture range for moving without causing good hedonic results.